Current and new concepts in the diagnosis and management of diabetic macular oedema - Jyothi, Sreedhar (Cranfield University, 2013)
Diabetic macular oedema, which can cause rapid visual deterioration, may not have early warning signs at times. Assessment of diabetic retinal complications is made chiefly by clinical examination combined with optical coherence tomography (OCT) and fundus fluoroscein angiography (FFA). However, assessment usually does not occur until the late stages of diabetic retinopathy (DR), and, as retinal neurologic changes precede clinical changes, as tested in this thesis, by the time clinical assessment is performed, much of the functional visual loss has already occurred. More robust diagnostic modalities are required to detect progression of retinopathy in the early stages, before irreversible damage has already happened, and advances in the treatment of diabetic macular oedema is imperative as the current standard treatment in the form of laser photocoagulation is ineffective in improving the vision as authenticated in the following chapters. In this thesis, both treatment and diagnostic strategies of diabetic macular oedema (DMO) are investigated. Although laser photocoagulation is effective in short term in treating diabetic macular oedema, its mechanism of action is unknown; is associated with considerable collateral damage; and long term visual prognosis is meagre at a mean change in visual acuity at 5 years of -5.23. The 3-year outcome was also inferior to the clinical trial results with more people gaining vision (≥ 15 letter gain) in the diabetic retinopathy clinical research network (DRCRN) group compared to this cohort (26% versus 9%). Furthermore, three times more patients lost vision (> 15 letter loss) in the real-life setting of this cohort compared to the clinical trial results of the DRCRN group (27% versus 8%, respectively). Therefore, improved preventative and treatment modalities are essential to prevent progression in the early stages and to improve functional vision in late stages. In an attempt to look for new treatment strategies, we hypothesized that retinal oxygenation by inhibition of dark adaptation in the rod photoreceptor, could possibly inhibit progression of diabetic maculopathy. Illuminated-mask treatment of individuals with early diabetic maculopathy revealed encouraging results that point to an inexpensive and non-invasive therapy. Whilst 19 out of 34 study eyes with cysts at the beginning of the trial improved, 11 out of 30 fellow eyes with no demonstrable cysts at the onset developed cystic macular changes towards the end of 6 month trial. In the final chapters the correlation of visual functions with anatomic appearance were examined. The results of functional assessments, including visual acuity, colour contrast sensitivity, and microperimetry, had variable relation to structural changes at the macula with OCT. Therefore, an urgent need remains for the development of reliable diagnostic and preventative tools for the early assessment and treatment of visual function defects related to diabetic macular oedema.